PRINCIPLES OF CLASSIFICATION OF COMPLEX SUBORDINATE SENTENCES IN THE KARAKALPAK LANGUAGE - F.i.o. - Seydullayeva Darigul Yuldashevna (Journals Park Publishing, 2022)
The given article deals with three principal classifications of compound sentences - functional (semantically), formal and structural-semantically. Having analyzed the principal classification of compound sentences is given in the Turkic languages. It was widely researched the problems of learning compound sentences in the Karakalpak language. Compound sentences aren’t still learned in the Karakalpak materials and this is the basis of the research.
Keywords: compound sentence, functional principal, formal principal, structural-semantically principal, subordinate clause.